Revealing Nanomechanical Domains and Their Transient Behavior in Mixed‐Halide Perovskite Films. (31st March 2021) - Mela, Ioanna; Poudel, Chetan; Anaya, Miguel; Delport, Géraud; Frohna, Kyle; Macpherson, Stuart; Doherty, Tiarnan A. S.; Scheeder, Anna; Stranks, Samuel D.; Kaminski, Clemens F.
Abstract: Halide perovskites are a versatile class of semiconductors employed for high performance emerging optoelectronic devices, including flexoelectric systems, yet the influence of their ionic nature on their mechanical behavior is still to be understood. Here, a combination of atomic‐force, optical, and compositional X‐ray microscopy techniques is employed to shed light on the mechanical properties of halide perovskite films at the nanoscale. Mechanical domains within and between morphological grains, enclosed by mechanical boundaries of higher Young's Modulus (YM) than the bulk parent material, are revealed. These mechanical boundaries are associated with the presence of bromide‐rich clusters as visualized by nano‐X‐ray fluorescence mapping. Stiffer regions are specifically selectively modified upon light soaking the sample, resulting in an overall homogenization of the mechanical properties toward the bulk YM. This behavior is attributed to light‐induced ion migration processes that homogenize the local chemical distribution, which is accompanied by photobrightening of the photoluminescence within the same region. This work highlights critical links between mechanical, chemical, and optoelectronic characteristics in this family of perovskites, and demonstrates the potential of combinational imaging studies to understand and design halide perovskite films for emerging applications such as photoflexoelectricity. Abstract : Bromide‐rich regions with a higher Young's Modulus form mechanical boundaries that define mechanical domains in mixed‐halide perovskite films. These mechanical domains are smaller than the morphological grains. Light soaking induces chemical reorganization that leads to a homogenization of the mechanical properties in the film, with photobrightening processes occurring concomitantly.